The views of Primary School principals on distance learning during the Covid-19 period - Τζημίρης Σπυρίδων; Καρούσιου Χριστιάνα (Education Sciences, 2022)
This empirical research investigates the views of school leaders of primary education, regarding the distance education implemented to support the educational needs of the student population, after the closure of schools due to the rapid spread at an unprecedented scale of coronavirus Covid-19. Semi-structured interviews were used to investigate their views and focused on the organisation of the distance education programme, the difficulties encountered in its implementation and suggestions for improving the situation in terms of supporting educational and learning needs. The results of the research revealed that the educational community was caught off guard regarding the decision to implement e-learning, as it took place without the proper preparation and training and the familiarisation with the implementation of similar practices. Nevertheless, the participants regarded e-learning as a dynamic alternative tool in times of crisis so that students would not be cut off from school procedures. In order to maximise the potentials of e-learning, they suggest that the state should provide the necessary technological support and equipment to students as well as to train school staff regarding the expanded possibilities of using new technologies in e-learning.